ANALYSIS OF BULLYING BEHAVIOR IN CLASS III STUDENTS OF AL-HIDAYAH PRIMARY SCHOOL - Ramadhani, Sri; Sitepu, Melyani Sari; Siregar, Dewani Oktaviani (Proceeding International Seminar of Islamic Studies, 2024)
Education serves two purposes: helping people become smart and encouraging them to become better. Making people smart is easier than pushing them to be better. Therefore, it can be said that moral issues are fundamental problems that fill human life at all times. Behavior that deviates from ethics, morals and law is often seen among pupils and students; moral decay is rife. One example is acts of violence that often occur today (bullying). This negative behavior shows the fragility of character in educational institutions as well as unsupportive environmental conditions. Bullying has become a familiar term for Indonesian people. The use of force to hurt a person or group of people verbally, physically or psychologically so that the victim feels depressed, traumatized and helpless is known as harassment. At Al Hidayah Elementary School there are behavioral deviations which include bullying, namely isolating so that a student feels traumatized and helpless. Based on problems related to behavioral deviations in class III students at SDS Al-Hidayah Terpadu Medan, this research focused on teachers' knowledge about bullying behavior and identifying forms of bullying behavior that occurred in class III SDS Al-Hidayah Terpadu Medan. Which aims to describe various forms of bullying behavior that occur in class III of SDS Al-Hidayah Terpadu Medan. This research uses a qualitative approach, this approach was chosen because this research is used to reveal the facts of events with explanations that are easy to understand and as they are. The qualitative research used was questionnaires, observations and interviews. The results of the research analysis show several facts that cause bullying behavior at SD AL HIDAYAH. Next, researchers will conduct research on how to stop bullying behavior.